Baseline associations between biomarkers, cognitive function, and self‐regulation indices in the Cognitive and Self‐regulatory Mechanisms of Obesity Study. (26th June 2021) - Hawkins, Misty A.W.; Keirns, Natalie G.; Baraldi, Amanda N.; Layman, Harley M.; Stout, Madison E.; Smith, Caitlin E.; Gunstad, John; Hildebrand, Deana A.; Vohs, Kathleen D.; Lovallo, William R.
Abstract: Objective: Understanding how biological, cognitive, and self‐regulatory factors are related to obesity, and weight regulation is clearly needed to optimize obesity prevention and treatment. The objective of this investigation was to understand how baseline biological, cognitive, and self‐regulatory factors are related to adiposity at the initiation of a behavioral weight loss intervention among treatment‐seeking adults with overweight/obesity. Methods: Participants ( N  = 107) in the Cognitive and Self‐regulatory Mechanisms of Obesity Study (Identifier‐NCT02786238) completed a baseline assessment with anthropometric, cardiometabolic, inflammatory, cognitive function, and self‐regulation measures as part of a larger on‐going trial. Data were analyzed with linear regression. Results: At baseline, body mass index, body fat percentage, and waist circumference (WC) were positively associated with fasting insulin and insulin resistance. Higher WC was related to higher fasting glucose and hemoglobin A1c (HbA1c). Higher glucose and insulin resistance levels were related to lower list sorting working memory. Higher glucose and HbA1c levels were negatively associated with reading scores. Cognitive function and self‐regulation indices were unrelated. Conclusions: In adults with overweight/obesity entering a weight loss treatment study: (1) elevated WC and associated glycemic impairment were negatively associated with cognition, (2) poorer executive function and reading abilities were associated with poorer glycemic control, and (3) objectively measured cognitive functions were unrelated to self‐reported/behavioral measures of self‐regulation. Such findings increase understanding of the relationships between adiposity, biomarkers, cognition, and self‐regulation at treatment initiation and may ultimately inform barriers to successful obesity treatment response.